The Use of Differentiated Instruction Strategies To Achieve Mastery Of Mathematical Communication Skills on Circular Material - Ariwibowo, M. Dwi (Integral (Jurnal Penelitian Pendidikan Matematika), 2024)
This study aims to determine the completeness of students' mathematical communication skills by using differentiated instruction strategies. This research is a type of pre-experimental research with a one-shot case study research design. This research was conducted on students in grade VIII of SMP Negeri 3 Adiwerna in the academic year 2023/2024. With a population of 320 students in class VIII, class 8-E was chosen as the experimental class with a sample size of 32 students. The results of hypothesis testing with the T-test and Proportion Test show that learning with differentiated instruction strategies has achieved mastery.